Surface Integrity Of LM6 Aluminum Metal Matrix Composite When Machined With High Speed Steel And Uncoated Carbide Cutting Tools - Abu Bakar, Mohd Hadzley; Raja Abdullah, Raja Izamshah; Md Ali, Mohd Amran; Kasim, Mohd Shahir; Sulaiman, Mohd Amri; Ahmad, Siti Sarah Nadia; Mohamad Raffi, Nurul Fatin (Universiti Malaysia Pahang, Malaysia, 2014)
-